The root canal morphology of mandibular anterior teeth and its correlation with the occurrence of three-rooted mandibular first molars - ZHU Peng, GU Yongchun, WU Yihan, XU Xiaoming (Kouqiang yixue)
Objective To study the root canal morphology of permanent mandibular anterior teeth and explore its correlation with the occurrence of three-rooted mandibular molars using cone beam computed tomographic (CBCT) imaging. Methods CBCT image data of 200 subjects were randomly collected from dental clinics. The root canal morphology of the mandibular anterior teeth was identified and classified by Vertucci’s classification, and the root length and labio-lingual dimension at the tooth neck level were measured. The occurrence of three-rooted mandibular first molars was examined as well. The concurrence rates of double-canaled anterior teeth and three-rooted mandibular first molars at each side, and concurrence rates of bilateral double-canaled anterior teeth and three-rooted mandibular first molars were calculated. Spearman correlation tests were applied to analyze the correlation between the double-canaled anterior teeth and three-rooted mandibular first molars, as well as the bilateral antimetric teeth. Results The incidence of double-canaled system was 10.4%, 18.6% and 6.5% in mandibular central incisors, lateral incisors and canines, respectively; the bilateral concurrence rates were 5.7%, 11.1% and 3.0%, respectively, and Spearman correlation coefficients (rho) were 0.487, 0.505 and 0.440 (P<0.01), respectively; gender difference and side difference were not detected (P>0.05). The frequency of three-rooted mandibular first molars was 24.6%; gender difference was not detected (P>0.05), while the incidence was significantly higher at the right side (29.0%) than the left side (20.3%)(P<0.05). The bilateral concurrence rate was 17.4%, and a moderate correlation was detected (rho=0.666, P<0.01). The concurrence rates between the double-canaled anterior teeth and three-rooted mandibular first molars at each side were very low (2.6%-7.6%), and Spearman correlation tests demonstrated that no correlation (P>0.05) could be detected between them. Conclusion The lateral incisors exhibited the highest incidence of two root canals among the mandibular anterior teeth. Additionally, there was no significant correlation between three-rooted mandibular first molars and double-canaled mandibular anterior teeth.